Proceedings of the 2nd ACM Workshop on Hot Topics on Wireless Network Security and Privacy 2013
DOI: 10.1145/2463183.2463194
|View full text |Cite
|
Sign up to set email alerts
|

Low-power secret-key agreement over OFDM

Abstract: Information-theoretic secret-key agreement is perhaps the most practically feasible mechanism that provides unconditional security at the physical layer to date. In this paper, we consider the problem of secret-key agreement by sharing randomness at low power over an orthogonal frequency division multiplexing (OFDM) link, in the presence of an eavesdropper. The low power assumption greatly simplifies the design of the randomness sharing scheme, even in a fading channel scenario. We assess the performance of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 28 publications
2
8
0
Order By: Relevance
“…We note that the variance of SKT increases with the maximum allocated power. This is accordance with the results of [10] where it has been shown that in the low SNR regime the optimal strategy is obtained by allocating the power to the best legitimate channels. We now consider reconciliation process implemented by LDPC codes obtained by uniform random puncturing of the code (256,128) of [11].…”
Section: Numerical Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…We note that the variance of SKT increases with the maximum allocated power. This is accordance with the results of [10] where it has been shown that in the low SNR regime the optimal strategy is obtained by allocating the power to the best legitimate channels. We now consider reconciliation process implemented by LDPC codes obtained by uniform random puncturing of the code (256,128) of [11].…”
Section: Numerical Resultssupporting
confidence: 91%
“…Reconciliation is based on the use of low density parity check (LDPC) codes, as also discussed in [9]. Application of channel-model based SKA to orthogonal division frequency multiplexing (OFDM) is also considered in [10], where it was shown that in a low power regime the strategy to allocate all transmit power on the sub-channel having the highest channel gain to the legitimate receiver is optimal and then a practical scheme was derived.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, in the application of PLS, consideration of OFDM systems is an important element. This problem was addressed by Renna et al [29], [30] by considering the physical layer of an OFDM transmitter/receiver pair in the presence of an eavesdropper that might either use an OFDM structure or choose a more complex receiver architecture. The analysis was made possible by modeling the system as a particular instance of a high dimensional MIMO wiretap channel.…”
Section: Ofdm Systemsmentioning
confidence: 99%
“…The interest for cryptographic applications of LDPC codes is continuously increasing [7]- [9], and they have already been shown to be useful also in secret key agreement schemes [10]. LDPC codes are able to achieve small security gaps over the AWGN wire-tap channel through puncturing [11], [12].…”
Section: Introductionmentioning
confidence: 99%